2022
DOI: 10.21203/rs.3.rs-1854127/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioactive Constituents of Safflower plant as potential inhibitors of mutant Leucine-rich repeat kinase 2 (LRRK2): Docking, Pharmacokinetics properties and Molecular Dynamics studies

Abstract: Background Parkinson’s disease has posed a global health threat with no disease-modifying treatment and prolonged use of available drugs such as Levodopa (L-dopa) causes debilitating side effects. This study focused on adopting in-silico approach to investigate the drug likeliness and pharmacokinetics of some Safflower plant phytochemicals as potential therapeutics. A manually curated library of 120 phytochemicals (from different parts of Safflower plant) was first screened virtually for adherence to the Lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…Furthermore, it was reported that a low energy complex and a compatible ligand can lead to potent activity (Agarwal and Mehrotra, 2016). Consequently, the recent molecular docking studies have demonstrated promising outcomes in terms of the binding affinity between CGBRE components and three targeted proteins, namely, EGFR, LRRK2, and HSP90A, which aligned with previous investigations conducted on these proteins (Mohamed et al, 2022;Omena-Okpowe et al, 2022). These findings suggest that CGBRE may be effective in the prevention or treatment of ulcerative colitis mediated by these proteins.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, it was reported that a low energy complex and a compatible ligand can lead to potent activity (Agarwal and Mehrotra, 2016). Consequently, the recent molecular docking studies have demonstrated promising outcomes in terms of the binding affinity between CGBRE components and three targeted proteins, namely, EGFR, LRRK2, and HSP90A, which aligned with previous investigations conducted on these proteins (Mohamed et al, 2022;Omena-Okpowe et al, 2022). These findings suggest that CGBRE may be effective in the prevention or treatment of ulcerative colitis mediated by these proteins.…”
Section: Discussionsupporting
confidence: 80%